2007
DOI: 10.1093/ajcn/86.1.206
|View full text |Cite
|
Sign up to set email alerts
|

Hardness (difficulty of chewing) of the habitual diet in relation to body mass index and waist circumference in free-living Japanese women aged 18–22 y

Abstract: Background: Animal studies suggest the beneficial effect of hardness of diet on body weight and adiposity. No human studies have examined hardness of diet in relation to obesity. Objective: We examined cross-sectional associations of hardness of the habitual diet with body mass index (BMI; in kg/m 2 ) and waist circumference in free-living humans. Design: Subjects were 454 female Japanese dietetic students aged 18 -22 y. Dietary hardness was assessed as an estimate of masticatory muscle activity for the habitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
70
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 26 publications
(32 reference statements)
1
70
0
Order By: Relevance
“…In the present study, the higher chewing power is related to the lower score of disinhibition in both non-obese and pre-obese participants. This may be related to the cross sectional observations reported that greater dietary hardness was associated with healthier dietary patterns, including lower energy and fat and higher protein and dietary fiber and associated with lower waist circumference in young adults [35]. Further study needs to confirm whether the activation of chewing muscle can stimulate the neuronal or cognitive inhibition of impulse eating and its efficacy against obesity.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, the higher chewing power is related to the lower score of disinhibition in both non-obese and pre-obese participants. This may be related to the cross sectional observations reported that greater dietary hardness was associated with healthier dietary patterns, including lower energy and fat and higher protein and dietary fiber and associated with lower waist circumference in young adults [35]. Further study needs to confirm whether the activation of chewing muscle can stimulate the neuronal or cognitive inhibition of impulse eating and its efficacy against obesity.…”
Section: Discussionmentioning
confidence: 95%
“…We speculate that in such conditions, involving unusually high levels of masseter muscle activity, IL-6 may be produced and function as a defense mechanism to maintain glucose homeostasis. Soft-food dietary habits are now seen as a health problem, and the importance of hard food is being re-evaluated (Oka et al 2003;Suzuki et al 2005;Murakami et al 2007). Possibly, IL-6 should be considered to be an emergency signal and/or as a factor that allows MM to sustain abnormally high levels of activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although modern diets feature soft foods which do not require extensive mastication (Murakami et al 2007), an easily chewable diet is thought to have unfavorable effects on the craniofacial region (Hanihara et al 1981;Varrela 1992). Many experimental studies using laboratory animals have investigated these effects; influence of liquid diet has been confirmed in the craniofacial skeleton (Ito et al 1988;Yamamoto 1996) and masseter muscles (Maeda et al 1990; Kitagawa et al 2004).…”
Section: Introductionmentioning
confidence: 99%